Increasing Awareness of Consumer Rights and Obligations in E-Commerce Transaction Activities - Handriyanto Igirisa; Mohamad Rusdiyanto U. Puluhulawa; Julius T. Mandjo (Estudiante Law Journal, 2022)
This study aims to determine and analyze how the role of YLKI Gorontalo Province in increasing awareness of consumer rights and obligations in e-commerce transaction activities. The method used in this research is empirical legal research with a qualitative approach. Based on the results of the study, it is shown that the role of YLKI Gorontalo Province in increasing awareness of consumer rights and obligations in e-commerce transaction activities, namely: (1) conducting information dissemination programs through social media, distributing banners or billboards, socialization or legal counseling; and (2) provide education at the time of the complaint. However, according to the author, the role of YLKI Gorontalo has not been maximal and comprehensive. . This can be see from the lack of informasion dissemination carried out by YLKI Gorontalo regarding the importance of knowledge of consumer right and obligations as stated in Article 4 and Article 5 of the UUPK, especially in conducting electronic commerce (e-commerce) as well as the lack of socialization carried out by YLKI Gorontalo, namely one times since actively running errands.